Field-Effect Transistors on Photonic Cellulose Nanocrystal Solid Electrolyte for Circular Polarized Light Sensing - Grey, Paul (2019)
The authors acknowledge the support from the FCT – Portuguese Foundation for Science and Technology through the Ph.D. scholarship SFRH/BD/125191/2016. The authors would like to acknowledge the European Commission under project NewFun (ERC‐StG‐2014, GA 640598) and BET‐EU (H2020‐TWINN‐2015, GA 692373). This work was also supported by the FEDER funds through the COMPETE 2020 Program, Portugal2020 project CelSmartSense number 17862 and the National Funds through the FCT – Portuguese Foundation for Science and Technology under the Project No. POCI‐01‐0145‐FEDER‐007688, Reference UID/CTM/50025, project FunPaper, reference EXPL/CTM‐NAN/1184/2013, project PapEl, reference PTDC/CTM‐NAN/5172/2014, project PTDC/CTM‐BIO/6178/2014 and M‐ERA‐NET2/0007/2016 (CellColor). S.N.F. acknowledges the MCTES, the European Social Funds, and the FCT for fellowships SFRH/BDP/78430/2011. D.G. acknowledges the support from the FCT – Portuguese Foundation for Science and Technology through the AdvaMTech PhD program scholarship PD/BD/52627/2014.